A review of applications of visual inspection technology based on image processing in the railway industry. Issue 3 (5th February 2020) - Liu, Scarlett; Wang, Quandong; Luo, Yiping
Abstract: In order to ensure the safety of railway transportation, it is necessary to regularly check for faults and defects in the railway system. Visual inspection technology is conducive to improving the low efficiency, poor economy and inaccurate detection results of traditional detection methods. This paper introduces the research and contribution of various scholars in the field of visual inspection, summarizes the application and development of visual inspection technology in the railway industry, and finally forecasts the future research direction of visual inspection technology.